2015
DOI: 10.1039/c5tb00285k
|View full text |Cite
|
Sign up to set email alerts
|

A primary study of poly(propylene fumarate)–2-hydroxyethyl methacrylate copolymer scaffolds for tarsal plate repair and reconstruction in rabbit eyelids

Abstract: A poly(propylene fumarate)-co-2-hydroxyethyl methacrylate (PPF–HEMA) copolymer scaffold was designed for tarsal plate repair and reconstruction in rabbit eyelids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…When examined histologically, the bioengineered scaffolds elicited changes suggestive of an acute, followed by chronic inflammatory response, which contrasted with minimal inflammatory changes around the ADM and blank defect controls. Gao et al [7] produced scaffolds composed of poly(propylene fumarate)-co-2-hydroxyethyl methacrylate (PPF-HEMA) that were characterised based on mechanical and degradation properties. The tensile moduli of the scaffolds were reported to be in the range 5-14 MPa, distinctly higher than those of tarsus tissue and the chitosan scaffolds produced here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When examined histologically, the bioengineered scaffolds elicited changes suggestive of an acute, followed by chronic inflammatory response, which contrasted with minimal inflammatory changes around the ADM and blank defect controls. Gao et al [7] produced scaffolds composed of poly(propylene fumarate)-co-2-hydroxyethyl methacrylate (PPF-HEMA) that were characterised based on mechanical and degradation properties. The tensile moduli of the scaffolds were reported to be in the range 5-14 MPa, distinctly higher than those of tarsus tissue and the chitosan scaffolds produced here.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue engineering represents the future of regenerative medicine and has huge potential to advance our current reconstructive techniques by producing highly specialised and personalised tissue replacements. To the best of our knowledge, there are only two previous studies that investigated the use of polymeric scaffolds for tarsal repair [6,7]. These studies used acellular polymer scaffolds as synthetic tarsal substitutes in rats and rabbits, and found that they were successful in supporting eyelid reconstruction and fibroblast growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biodegradable polyurethane (PPFU/HDI: 1.6 + Lys‐OMe, M n : 29.2 kDa, M w : 83.8 kDa) used in this experiment was synthesized by our laboratory . N ‐acryloyl‐ l ‐valine, N ‐acryloyl‐ d ‐valine, methyl 2‐(butylthiocarbonothioylthio)propanoate (RAFT agent, MCEBTTC), and mercapto‐functionalized poly( N ‐acryloyl‐ l ( d )‐valine) ( l ( d )‐PAV‐SH, M w : 1.8 kDa, Figure S1, Supporting Information) were synthesized according to the procedures described in the Supporting Information.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…We have previously synthesized novel polyurethanes based on poly(propylene fumarate) (PPFUs), which have been used for biomedical applications like tarsal plates . Compared to other types of degradable materials such as poly(lactic acid), poly(lactic‐ co ‐glycolic acid) and poly( ε ‐caprolactone), the PPFUs possess various advantages, such as good mechanical properties, easy modification, and low toxicity of the degradation products .…”
Section: Introductionmentioning
confidence: 99%